Interventions at presentation and discharge for patients with acute exacerbation of chronic obstructive pulmonary disease to reduce unnecessary admissions and readmissions: A scoping review protocol - Rachel MacDonell; Orla Woods; Lucia Prihodova (Wiley, 2020)
Abstract Aim This scoping review will gather existing evidence on specific interventions at presentation and discharge which aim to standardize care and/or reduce unnecessary admissions and/or readmissions to hospital for patients presenting with acute exacerbation of chronic obstructive pulmonary (airways) disease. Design Scoping review of relevant literature from January 2000-March 2019. Methods Database searches for primary evidence in peer‐reviewed journals will be conducted electronically using Web of Science, EMBASE (Elsevier) and PUBMED. Eligibility criteria will include hospital‐based interventions for presentations of acute exacerbation of chronic obstructive pulmonary disease with outcomes specific to standardizing care or reducing unnecessary admissions or readmissions. Abstract, full‐text screening and data extraction will be completed independently by a panel of expert reviewers. Results We aim to identify current interventions and improvement approaches in acute exacerbation of chronic obstructive pulmonary (airways) disease care that have an impact on admission and discharge processes or readmissions. Recommendations as a result of this review will aid the design and development of future improvement intervention.